PD-1/PD-L1 immune checkpoint therapy demonstrates favorable safety profile in patients with autoimmune and cholestatic liver disease - Kocheise, Lorenz; Piseddu, Ignazio; Vonderlin, Joscha; Tjwa, Eric T.; Buescher, Gustav; Meunier, Lucy; Goeggelmann, Pia; Fianchi, Francesca; Dumortier, Jérôme; Riveiro Barciela, Mar; Gevers, Tom J. G.; Terziroli Beretta-Piccoli, Benedetta; et al. (Frontiers in Immunology, 2024)
Introduction: Immune checkpoint inhibitors (ICI) have revolutionized the treatment of many malignancies in recent years. However, immune-related adverse events (irAE) are a frequent concern in clinical practice. The safety profile of ICI for the treatment of malignancies in patients diagnosed with autoimmune and cholestatic liver disease (AILD) remains unclear. Due to this uncertainty, these patients were excluded from ICI clinical trials and ICI are withheld from this patient group. In this retrospective multicenter study, we assessed the safety of ICI in patients with AILD. Methods: We contacted tertiary referral hospitals for the identification of AILD patients under ICI treatment in Europe via the European Reference Network on Hepatological Diseases (ERN RARE-LIVER). Fourteen centers contributed data on AILD patients with malignancies being treated with ICI, another three centers did not treat these patients with ICI due to fear of irAEs. Results: In this study, 22 AILD patients under ICI treatment could be identified. Among these patients, 12 had primary biliary cholangitis (PBC), five had primary sclerosing cholangitis (PSC), four had autoimmune hepatitis (AIH), and one patient had an AIH-PSC variant syndrome. Eleven patients had hepatobiliary cancers and the other 11 patients presented with non-hepatic tumors. The applied ICIs were atezolizumab (n=7), durvalumab (n=5), pembrolizumab (n=4), nivolumab (n=4), spartalizumab (n=1), and in one case combined immunotherapy with nivolumab plus ipilimumab. Among eight patients who presented with grade 1 or 2 irAEs, three demonstrated liver irAEs. Cases with grades ≥ 3 irAEs were not reported. No significant changes in liver tests were observed during the first year after the start of ICI. Discussion: This European multicenter study demonstrates that PD-1/PD-L1 inhibitors appear to be safe in patients with AILD. Further studies on the safety of more potent dual immune checkpoint therapy are needed. We conclude that immunotherapy should not categorically be withheld from patients with AILD.